Expansion of a Breastfeeding Promotion Network for Sick Infants and Children Across 13 Health Service Regions in Thailand - Siriluck Thavonvattana; Benjamas Thussanasupap; Hataitip Somdam (Journal of Human Lactation, 2026)
Breastfeeding is a cost-effective intervention that improves survival and long-term health outcomes, yet policy mechanisms to support breastfeeding among medically ill infants and children are underdeveloped in many health systems. In Thailand, national breastfeeding promotion policies have historically focused on healthy term infants, resulting in fragmented and inequitable support for infants requiring hospital-based care. This study examines the development and national scale-up of a network-based breastfeeding promotion policy focused on breastfeeding support for sick infants and children, implemented across 13 health service regions. Guided by Stringer’s action research framework, international evidence was systematically reviewed and adapted to the national context through interprofessional engagement, regional pilot implementation, and iterative policy learning. Spatz’s Ten Steps to Promote and Protect Human Milk and Breastfeeding in Vulnerable Infants were operationalized through coordinated hospital workflows, supported by regional knowledge exchange and field-based expert mentorship. Implementation across 74 pilot hospitals generated sustained improvements in policy-relevant indicators, including the rate of exclusive breastfeeding at discharge and the rate of exclusive breastfeeding at 6 months among medically ill infants. These outcomes directly informed the integration of breastfeeding indicators into national inspection and accountability mechanisms, representing a transition from project-based implementation to formal policy institutionalization. This policy experience demonstrates how regionalized health systems can translate evidence into scalable action for vulnerable populations. By aligning service delivery, governance structures, and performance monitoring, the Thai case offers transferable insights for strengthening national breastfeeding promotion policies in complex health systems and advancing equitable care for medically ill infants and children.